1994
DOI: 10.1111/j.1365-2125.1994.tb04295.x
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective disposition of flurbiprofen in healthy subjects following administration of the single enantiomers.

Abstract: Plasma concentrations of the enantiomers of flurbiprofen were measured following oral administration of (S)-flurbiprofen 50 mg and (R)-flurbiprofen 50 mg and 100 mg to sixteen healthy subjects. Chiral inversion did not occur to a measurable exent. Significantly higher values of AUC (55.2 ± 17.0 vs 44.6 ± 11.2 ig ml-' h) elimination half-life (5.6 ± 1.4 vs 4.0 ± 1.0 h) and mean residence time (7.5 ± 1.6 vs 5.7 ± 1.2 h) were observed after 50 mg (S)-flurbiprofen as compared with 50 mg (R)-flurbiprofen. With the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 10 publications
(23 reference statements)
4
41
0
Order By: Relevance
“…In the present study, the mean plasma concentration was 3331 ng ml -1 in the patients receiving orally administered flurbiprofen. This result is comparable with the previous data [9,[11][12][13][14]. Concerning topical application with the same two tapes as used in the present study, it was reported that the Cmax in the plasma was 870 ng ml -1 at the tmax of 11.6 h [8].These data are also comparable with the present result (1369 ng ml -1 ) on the plasma concentration in the patients receiving topically applied flurbiprofen.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the present study, the mean plasma concentration was 3331 ng ml -1 in the patients receiving orally administered flurbiprofen. This result is comparable with the previous data [9,[11][12][13][14]. Concerning topical application with the same two tapes as used in the present study, it was reported that the Cmax in the plasma was 870 ng ml -1 at the tmax of 11.6 h [8].These data are also comparable with the present result (1369 ng ml -1 ) on the plasma concentration in the patients receiving topically applied flurbiprofen.…”
Section: Discussionsupporting
confidence: 83%
“…After oral administration of a tablet containing 40 mg flurbiprofen, the Cmax in the plasma was 5600 ng ml -1 and the tmax was 1.4 h [9]. After oral administration of a tablet containing 50 mg flurbiprofen, several studies reported that the Cmax ranged from 4200 to 8200 ng ml -1 and that the tmax ranged from 1.3 to 2.8 h [11][12][13][14]. In the present study, the mean plasma concentration was 3331 ng ml -1 in the patients receiving orally administered flurbiprofen.…”
Section: Discussionmentioning
confidence: 99%
“…This was reported for the antiarrhythmic drug disopyramide [40], in which individual enantiomers yielded R:S enantiomer ratios for Cl and V d of close to 1 when given as individual enantiomers, whereas racemate resulted in R:S ratios of 1.6 and 1.8 for Cl and V d , respectively. Similarly in rat [41], but not in human [42], an enantiomerenantiomer interaction has been noted for the nonsteroidal antiinflammatory drug flurbiprofen, with displacement of R enantiomer by antipode.…”
Section: Distributionmentioning
confidence: 93%
“…However, there is a need to compare (R)-flurbiprofen directly with other non-opioid analgesics like paracetamol or with opioids. Chiral inversion of either (R)-or (S)-flurbiprofen to its optical antipode did not occur to a measurable extent [5]. Thus, the analgesic effects observed after administration of (R)-flurbiprofen have to be attributed to this enantiomer.…”
Section: Discussionmentioning
confidence: 90%
“…The pharmacokinetic parameters of the flurbiprofenenantiomers are published elsewhere [5]. Neither (R)-nor (S)-flurbiprofen was inverted to its optical antipode to a measurable extent.…”
Section: Plasma Concentrations Offlurbiprofenmentioning
confidence: 99%